Perioperative comparison of whether the liver was lifted out of the abdominal cavity in Kasai surgery - Xu, Ke; Gao, Juan; Chen, Xiaoyi; Fang, Yifan; Wu, Dianming; Lin, Yu (Frontiers in Pediatrics, 2025)
ObjectiveTo compare the perioperative effect of whether the liver is lifted out of the abdominal cavity during Kasai surgery in patients with biliary atresia type III.MethodsWe retrospectively analyzed 29 males and 33 females aged 2.2 ± 0.6 months who underwent kasai surgery from June 2019 to December 2022 at Fujian Provincial Children's Hospital. Among the 62 children with the liver not lifted out of the abdominal cavity into the experimental group (n = 31), and those with the liver lifted out of the abdominal cavity into the control group (n = 31). We compared the operation time, surgical incision length, intraoperative blood pressure and body temperature fluctuations, average daily peritoneal drainage, postoperative length of hospital stay, postoperative complications, postoperative total bilirubin level, and autologous liver survival rate between the two groups.ResultsThe length of the surgical incision in the control group (7.5 ± 1.2 cm) was longer than that in the experimental group (6.7 ± 1.1 cm), and the difference was statistically significant (t = 2.88, P = 0.005). The fluctuations in blood pressure in the control group (before and after the liver was lifted out of the abdominal cavity) (24.3 ± 7.7 mmHg) were greater than that in the experimental group (before and after hooking to expose the hilar area) (20.2 ± 6.0 mmHg), which was a statistically significant difference (t = 2.32, P = 0.023). The temperature fluctuations in the control group (before and after the liver was lifted out of the abdominal cavity) (0.3 ± 0.1°C) was greater than that in the experimental group (before and after the liver was lifted out of the abdominal cavity) (0.1 ± 0.1°C), showing a statistically significant difference (t = 8.19, P = 0.000). The average daily abdominal drainage in the control group was 71.3 ± 33.5 ml, which was greater than that in the experimental group (49.2 ± 49.6 ml), and the difference was statistically significant (t = 2.06, P = 0.044). The number of days of postoperative hospital stay in the control group (18.2 ± 4.8 days) was significantly more than that in the experimental group (15.8 ± 3.8 days), with a statistically significant difference (t = 2.18, P = 0.033).ConclusionIn children with biliary atresia type III, the liver is not lifted out of the abdominal cavity during Kasai surgery increases the safety of surgery and reduces the length of hospital stay.